2022
DOI: 10.1021/acs.jpcc.2c00626
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Critical Synthetic Parameters for Nanoscale ε-Fe2O3 and Their Influence on Magnetic Behaviors

Abstract: An intermediate polymorph of iron oxide, ε-Fe2O3, has attracted significant attention due to its giant coercive field (H c) and potential applications in high-frequency millimeter-wave absorption and high-density magnetic recording. However, the fabrication of ε-Fe2O3 with high phase purity is still a challenge due to complicated synthetic procedures and a large variety of reaction parameters. Here, we have identified critical reaction parameters to improve the phase purity of ε-Fe2O3, and the effects of all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Among numerous iron oxide polymorphs, the most intriguing one is the metastable orthorhombic ε-Fe 2 O 3 phase, which does not exist in the bulk form. Epsilon ferrite is a ferrimagnet with a huge magnetocrystalline anisotropy that is responsible for the values of coercive force exceeding 2 T. Having attracted a lot of attention during the past few years [5][6][7], epsilon ferrite in the form of nanofilms [8][9][10] and nanoparticles [11][12][13][14] was shown to exhibit a complicated magnetic structure with four magnetic sub-lattices and room-temperature (RT) multiferroic behavior [15], which has not been observed in other simple metal oxides. Its large magnetic coercivity and proven magneto-electric coupling make this material ideal for the creation of novel oxide-based ferroic-on-semiconductor devices for spintronic applications, including low-power consumption magnetic media storage devices [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among numerous iron oxide polymorphs, the most intriguing one is the metastable orthorhombic ε-Fe 2 O 3 phase, which does not exist in the bulk form. Epsilon ferrite is a ferrimagnet with a huge magnetocrystalline anisotropy that is responsible for the values of coercive force exceeding 2 T. Having attracted a lot of attention during the past few years [5][6][7], epsilon ferrite in the form of nanofilms [8][9][10] and nanoparticles [11][12][13][14] was shown to exhibit a complicated magnetic structure with four magnetic sub-lattices and room-temperature (RT) multiferroic behavior [15], which has not been observed in other simple metal oxides. Its large magnetic coercivity and proven magneto-electric coupling make this material ideal for the creation of novel oxide-based ferroic-on-semiconductor devices for spintronic applications, including low-power consumption magnetic media storage devices [16].…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] It could also be shown that the addition of alkaline earth metal ions, such as Ca 2 + , Sr 2 + or Ba 2 + , in the synthesis medium favors the stabilization of the ɛ-Fe 2 O 3 phase and induces a morphology change of the formed nanoparticles from spherical to rodlike. [19,[26][27][28][29] Besides the difficulties to obtain the pure ɛ-Fe 2 O 3 phase, the crystal structure is not solely responsible for the magnetic properties. The magnetic behavior also depends on the particle size.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is also possible to directly use γ‐Fe 2 O 3 nanoparticles and thermally treat them, inducing their transformation into the ϵ‐Fe 2 O 3 phase [24,25] . It could also be shown that the addition of alkaline earth metal ions, such as Ca 2+ , Sr 2+ or Ba 2+ , in the synthesis medium favors the stabilization of the ϵ‐Fe 2 O 3 phase and induces a morphology change of the formed nanoparticles from spherical to rod‐like [19,26–29] …”
Section: Introductionmentioning
confidence: 99%